A Clinicopathological Analysis of Soft Tissue Sarcoma with Telangiectatic Changes. (29th December 2015) - Kobayashi, Hiroshi; Ae, Keisuke; Tanizawa, Taisuke; Gokita, Tabu; Motoi, Noriko; Matsumoto, Seiichi
Abstract : Background . Soft tissue sarcoma with a hemorrhagic component that cannot be easily diagnosed by needle biopsy is defined here as soft tissue sarcoma with telangiectatic changes (STST). Methods . We retrospectively reviewed clinicopathological data of STST from 14 out of 784 patients (prevalence: 1.8%) with soft tissue sarcoma. Results . Tumors were found mostly in the lower leg. Histological diagnoses were undifferentiated pleomorphic sarcoma (n = 5 ), synovial sarcoma (n = 5 ), epithelioid sarcoma (n = 2 ), and malignant peripheral nerve sheath tumor and fibrosarcoma (n = 1 ). No history of trauma to the tumor site was recorded in any patient. Needle aspiration transiently reduced the tumor volume, but subsequent recovery of tumor size was observed in all cases. Out of 14 patients, 9 presented with a painful mass. MRI characteristics included intratumoral nodules (64.3%). The local recurrence rate was 14.3%, and the 2-year event-free survival rate was poorer (50%) than that of most sarcomas. Conclusions . STST is unique in its clinicopathological presentation. Painful hematomas without a trauma history, intratumoral nodules within a large hemorrhagic component, and subsequent recovery of tumor size after aspiration are indicative of the presence of STST.